Chasing Mythical Beasts The Reception of Ancient Monsters in Children's and Young Adults' Culture - Marciniak, Katarzyna (Universitätsverlag Winter, 2020)
Classical Antiquity is strongly present in youth culture globally. It accompanies children during their initiation into adulthood and thereby deepens their knowledge of the cultural code based on the Greek and Roman heritage. It enables intergenerational communication, with the reception of the Classics being able to serve as a marker of transformations underway in societies the world over. The team of contributors from Europe, North America, Africa, Asia, Australia, and New Zealand focuses on the reception of mythical creatures as the key to these transformations, including the changes in human mentality. The volume gathers the results of a stage of the programme 'Our Mythical Childhood', supported by an Alexander von Humboldt Foundation Alumni Award for Innovative Networking Initiatives and an ERC Consolidator Grant. Thanks to the multidisciplinary character of its research (Classics, Modern Philologies, Animal Studies) and to the universal importance of the theme of childhood, the volume offers stimulating reading for scholars, students, and educators, as well as for a wider audience.